Experimental characterization of nozzle flow expansions of siloxane MM for ORC turbines applications. (1st March 2021) - Cammi, Giorgia; Conti, Camilla Cecilia; Spinelli, Andrea; Guardone, Alberto
Abstract: This paper reports extensive experimental results characterizing the supersonic expansion of organic vapor MM (hexamethyldisiloxane, C 6 H 18 O S i 2 ) in conditions representative of actual Organic Rankine Cycle turbine operation, in the close proximity of the liquid-vapor saturation curve. Experiments were conducted on the Test Rig for Organic VApors, at the Laboratory of Compressible fluid dynamics for Renewable Energy Applications of Politecnico di Milano. A planar nozzle featuring a design exit Mach number of 1.6 was characterized by measuring total pressure, total temperature, static pressures along the nozzle axis and by schlieren visualizations. The non-ideal influence of inlet total conditions on nozzle expansions was verified by gathering data exhibiting total compressibility factor Z T ranging from 0.39 (strongly non-ideal) to 0.98 (almost ideal conditions). Pressure ratio measured at the lowest Z T exceeded by 10 % –20 % the one at highest Z T along the whole nozzle. An extensive experimental dataset was analyzed to assess the influence of both total compressibility factor Z T and total fundamental derivative of gasdynamics Γ T on the non-dimensional pressure distribution along the nozzle axis. It was investigated whether one parameter only can univocally identify a non-dimensional nozzle expansion. Significant validation data for simulation codes and design tools are provided for MM and for siloxanes in general. Highlights: Experimental characterization of non-ideal expansions for ORC turbine applications. Non-ideal isentropic nozzle flow of hexamethyldisiloxane (MM). Influence of total conditions on non-ideal isentropic expansion process. Compressibility factor and fundamental derivative of gasdynamics role on expansions. One-dimensional non-ideal isentropic expansions of vapors for ORC applications.